Persepsi Siswa Tentang Penggunaan Metode Demonstrasi Hubungannya Dengan Kualitas Pembelajaran Pendidikan Agama Islam - Nissa Shafira (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to determine (1) the quality of Islamic religious education learning (2) the use of demonstration methods (3) students' perceptions of the use of demonstration methods in relation to the quality of Islamic religious education learning at SMPN 3 Pusakaranagara, Subang Regency. This study uses a quantitative approach. Based on the research results obtained, it was concluded that the variable X obtained an average value of 4.19, with positive qualifications because it was in the interval 3.51-4.50, the variable Y obtained a value of 4.32 with high qualifications because it was in the interval 3, 51-4.50 and the last variable XY is (a) the value of the correlation coefficient is 0.53 with sufficient qualifications because it is in the interval 0.5-0.69, (b) The hypothesis is accepted. This means that there is a relationship between students' perceptions of the use of demonstration methods with the quality of Islamic religious education learning, because it shows tcount 3,475 > t table 1,692 and (c) the degree of influence between variable X and variable Y there is a significant relationship and has a degree of influence of 16% which it can be interpreted that there are 84% of other factors that can affect the quality of Islamic religious education learning.